Research Progress on the Impacts of Social Isolation and Loneliness on the Health of the Elderly - Elisa M. Carter; Ryan D. Simmons; Megan L. Henderson; Julia A. Bennett (Journal of Public Health and Preventive Medicine, 2026)
Social isolation and loneliness have emerged as critical public health concerns affecting older adults worldwide. Despite being distinct concepts—social isolation referring to the objective lack of social connections and loneliness representing the subjective distress of feeling alone—both conditions are associated with profound adverse effects on physical and mental health. This narrative review synthesizes current research on the conceptual definitions, measurement tools, health impacts, intervention strategies, and future research directions regarding social isolation and loneliness in the elderly population. Evidence consistently demonstrates associations with increased risks of depression, cognitive decline, cardiovascular disease, and mortality. Various interventions, including cognitive behavioral therapy, social engagement programs, and technology-mediated approaches, show promise in mitigating these conditions. However, significant methodological limitations persist, necessitating more rigorous longitudinal and randomized controlled trials to establish causal relationships and optimize intervention efficacy.